Simultaneous Determination of Furosemide, Carbamazepine, Diazepam and Carvedilol in Quaternary Mixture via Derivative Spectrophotometry - Nahla. A. Alassaf (Journal of Global Pharma Technology, 2016)
Quick and accurate quaternary mixture resolution of furosemide (FURO), carbamazepine (CARB), diazepam (DIAZ) and carvedilol (CARV) by using derivative spectrophotometric method was performed. FURO and CARV were determined by means of first (D1), second (D2), third (D3) and fourth (D4) derivative spectrophotometric methods,  CARB was determined by using D1, D2, D3 derivatives, while D1 and D2 were used for the determination of DIAZ. The recommended methods were verified using laboratory prepared mixtures and then successfully applied for the pharmaceutical formulations analysis of the cited drugs. The results obtained revealed the efficiency of the proposed methods as quantitative tool of analysis of the quaternary mixture with no requirements for sample neither pretreatment nor preliminary separation of analytes from the pharmaceutical preparations.Keywords: Derivative spectrophotometry; Furosemide; Carbamazepine; Diazepam; Carvedilol.